STUDI SISTEM KEAMANAN DATA DENGAN METODE PUBLIC KEY CRYPTOGRAPHY - Dadang Haryanto; Sarmidi - (LPPM STMIK DCI, 2014)
As had been widely circulated special program data protection either freeware, shareware, and commercial excellent. In general, the program not only provides one method alone, but some kind so that we can choose who we think is the most secure. One method is public key encryption criptography. To date the authors have noticed many data protection programs that have been published in magazines or Antivirus Mikrodata, but rarely well enough so that it can be trusted to protect important data.Security is a vital component in electronic data communication. There are still many who do not realize that the safety (security) is an important component that is not cheap. Cryptographic technology also plays an important role in the communication process, which is used to perform encryption (scrambling) of data transacted during the journey from source to destination and also perform decryption (recast) the data that has been scrambled. Various systems have been developed as a system private key and public key. Mastery of popular algorithms used to secure the data is also very important. Example - examples of these algorithms are: DES, IDEA, RC5, RSA, and ECC (Elliptic Curve Cryptography). Research in this field in college is an important thing.Cryptography is the science and art of message storage, data, or information securely. Cryptography (Cryptography) is derived from the Greek word meaning Graphia Crypto and secret writing. Cryptography is the science that studies the secret writing. Cryptography is part of a branch of mathematics called Cryptology. Cryptography aims to maintain the confidentiality of the information contained in the data so that the information can not be known by any unauthorized party.Key Word : Data Security, Cryptography.